2011
DOI: 10.1007/s11910-011-0186-y
|View full text |Cite
|
Sign up to set email alerts
|

NMDA Receptor Antibody Encephalitis

Abstract: N-methyl-D-aspartate receptor (NMDAR) antibody encephalitis is a recently described immunotherapy-responsive panencephalitis with characteristic features that include a psychiatric onset and a later movement disorder. This entity was first described as a paraneoplastic phenomenon in young women with ovarian teratomata. However, more recently it has become clear that the majority of patients, particularly children, do not harbor a tumor and that males can also be affected. With the development of the NMDAR anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
105
1
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 35 publications
1
105
1
10
Order By: Relevance
“…GluR3, one subtype of antibodies to NMDA, was detected in the patients of 3 severe epilepsies: RE, noninflammatory focal epilepsy and "catastrophic" epilepsy [68-70]. With the development of the NMDAR antibody assay, now available worldwide, a few patients with classical limbic encephalitis(LE) and early psychosis and epilepsy have also been found to harbor these antibodies [71]. Antibody levels correlate with the clinical severity of the disease in individual patients, and the antibodies have been shown to substantially reduce NMDAR on hippocampal neurons both in vitro and in vivo , supporting the likely direct pathogenicity of the NMDAR antibodies [72].…”
Section: Roles Of Immune and Inflammation In Drementioning
confidence: 99%
“…GluR3, one subtype of antibodies to NMDA, was detected in the patients of 3 severe epilepsies: RE, noninflammatory focal epilepsy and "catastrophic" epilepsy [68-70]. With the development of the NMDAR antibody assay, now available worldwide, a few patients with classical limbic encephalitis(LE) and early psychosis and epilepsy have also been found to harbor these antibodies [71]. Antibody levels correlate with the clinical severity of the disease in individual patients, and the antibodies have been shown to substantially reduce NMDAR on hippocampal neurons both in vitro and in vivo , supporting the likely direct pathogenicity of the NMDAR antibodies [72].…”
Section: Roles Of Immune and Inflammation In Drementioning
confidence: 99%
“…6 The mechanism by which these antibodies traverse the bloodbrain barrier is not completely understood, but likely requires some disruption of the barrier in order to trigger anti-NMDAR encephalitis. 8,9 Non-paraneoplastic cases evidently involve other unknown stimuli for NMDAR antibody synthesis-one report has suggested that subunits of the NMDAR are expressed by normal ovarian tissue, something which may explain the female predilection even in the cohort unaffected by teratomas. 10 Most patients with anti-NMDAR encephalitis are female and young (median age 23 years), although men and children are also affected.…”
Section: Commentarymentioning
confidence: 99%
“…10 Most patients with anti-NMDAR encephalitis are female and young (median age 23 years), although men and children are also affected. 8,9,11 While the exact incidence of anti-NMDAR encephalitis is still unknown, the increasing number of case reports suggests that it may be more frequent than any other type of paraneoplastic encephalitis. 12 The majority of patients with anti-NMDAR encephalitis experience an antecedent infectious prodrome (eg, diarrheal illness or upper respiratory infection [URI]), followed 10-20 days later by progressive neuropsychiatric and behavioral symptoms which include confusion, memory deficits, impaired responsiveness, seizures, central hypoventilation, and signs of autonomic instability (tachycardia, tachypnea, diaphoresis, cardiac dysrhythmia, blood pressure instability, and dysthermia).…”
Section: Commentarymentioning
confidence: 99%
See 2 more Smart Citations